2020
DOI: 10.3390/s21010190
|View full text |Cite
|
Sign up to set email alerts
|

Management of Fertigation in Horticultural Crops through Automation with Electrotensiometers: Effect on the Productivity of Water and Nutrients

Abstract: Water and nutrient requirements of horticultural crops are influenced by different factors such as: Type of crop, stage of development and production system. Although greenhouse horticultural crops are more efficient in the use of water and fertilizers compared to other production systems, it is necessary increase efficiency for which individualized fertigation strategies must be designed for each greenhouse. The automation of fertigation based on the level of soil moisture allows optimization of management. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…The higher EC in T100 could be due to a higher salt accumulation in the soil since irrigation by means of tensiometers at the above-mentioned matric potential considerably reduces the quantities of leaching. The activation of fertigation with a threshold value of soil matric tension −22 kPa allows no drainage, as shown by the research carried out in our cultivation area [26,27]. EC of saturated extract of soil obtained in T50 (2.79 dS•m −1 ), being similar to the electric conductivity (EC) of the nutritive solution used (2.40 dS•m −1 ), which indicates an optimal use of the nutrients provided in T50.…”
Section: Soil Analysismentioning
confidence: 55%
“…The higher EC in T100 could be due to a higher salt accumulation in the soil since irrigation by means of tensiometers at the above-mentioned matric potential considerably reduces the quantities of leaching. The activation of fertigation with a threshold value of soil matric tension −22 kPa allows no drainage, as shown by the research carried out in our cultivation area [26,27]. EC of saturated extract of soil obtained in T50 (2.79 dS•m −1 ), being similar to the electric conductivity (EC) of the nutritive solution used (2.40 dS•m −1 ), which indicates an optimal use of the nutrients provided in T50.…”
Section: Soil Analysismentioning
confidence: 55%
“…Santesteban et al (2016) reported that thermal images obtained from drone mount high-resolution camera provides accurate results on water status in the vineyard. Use of electrotensiometers for automation of irrigation in greenhouse was studied by Contreras et al (2021) in which demand-based fertigation dosage was supplied to sweet pepper, resulting in increased yield, water productivity and nutrient productivity without drainage. Recent studies have pointed that according to soil water availability and atmospheric demand, stem diameter increases or shrinks daily and these trunk variations can be measured using dendrometers, which is helpful for scheduling irrigation (Hahn et al, 2021).…”
Section: Application Of Ai In Automated Irrigationmentioning
confidence: 99%